Perhitungan Efektivitas Gardu Traksi Krl Lintas Manggarai - Bogor - P., Mariana Diah; Putra, feby Wiratama (Politeknik Perkeretaapian Indonesia Madiun, 2019)
Commuter line in PT Kereta Commuter Indonesia (KCI) is a means of transportation that transports passengers in Jabodetabek. In the Bogor-Manggarai crossing, several Traction substations are supplied. This study aims to find out how the capacity of substation power capacity in Bogor - Manggarai crossing towards the loading of the current Commuter line operating pattern and how the capacity of substation carrying capacity to increase the loading of KRL operating patterns at peak hour. For this reason, primary and secondary data are analyzed using the calculation formula. Among them: total Commuter line weight, tractive substation power capacity in the Manggarai-Bogor crossroad, power capacity based on headway, power capacity based on maximum current, required capacity, and cross capacity used on multiple lines. It can be concluded that the capacity of the cross-Manggarai-Bogor electric power in the normal 4-minute headway according to GAPEKA 2017 can be fulfilled by the Bojonggede Traction Station. And at peak hours conditions Bojonggede Traction substation can support with 3.75 minutes headway and can be reduced to 3 to 2 minutes.